2006
DOI: 10.1590/s0101-81752006000100016
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da história de vida de Bryconamericus microcephalus (Miranda Ribeiro) (Characiformes, Characidae) de um riacho costeiro de Mata Atlântica, Ilha Grande, Rio de Janeiro, Brasil

Abstract: Revista Brasileira de Zoologia 23 (1): 228-233, março 2006Dentre os principais aspectos que compõem a estratégia reprodutiva das espécies de peixes, destacam-se o dimorfismo sexual, tamanho dos ovos, fecundidade e período reprodutivo (MATTHEWS 1998). O entendimento de tais parâmetros pode ser considerado como o primeiro passo para o estabelecimento dos principais padrões da história de vida de peixes e a determinação de padrões recorrentes, normalmente, facilita previsões de comportamento em dada área zoogeogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 13 publications
0
18
0
3
Order By: Relevance
“…Larger females can allocate more energy to their offspring Mazzoni & Silva, 2006;Mai et al, 2007). However, the increase of embryo number with increase in female size reduces the survival probability of females; if the mean size of embryos is not reduced, then the large offspring of larger females may lead to death of the female.…”
Section: Discussionmentioning
confidence: 99%
“…Larger females can allocate more energy to their offspring Mazzoni & Silva, 2006;Mai et al, 2007). However, the increase of embryo number with increase in female size reduces the survival probability of females; if the mean size of embryos is not reduced, then the large offspring of larger females may lead to death of the female.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various families of fishes found in the upper Parana River, Characidae is the most diverse among the Characiformes, in which the genre Bryconamericus included on the "Insertae Sedes" (Mazzoni & Silva 2006). Studies about population ecology of small fishes in the floodplain portion of the upper Paraná River are few, except for those by Benedito-Cecilio et al (1997), who analyzed the length/weight relationship for fish species from Itaipu Reservoir; Lizama & Ambrósio (1999, discussing population aspects of nine species in the floodplain area of the upper Paraná basin; Lizama & Ambrósio (2003), analyzing the mortality and recruitment pattern of Moenkhausia intermedia; Piana et al (2006), quantifying the importance of environmental factors in density variation of Serrapinnus notomelas; and Lourenço et al (2008), analyzing the length/weight relationship, recruitment and mortality of S. notomelas and B. stramineus in streams of the lower Ivinhema River basin and Benitez & Súarez (2009) analyzing population parameters for S. notomelas in middle Ivinhema River Basin.…”
Section: Introductionmentioning
confidence: 99%
“…The highest correlation was found between fecundity and gonad mass in the headwaters and between fecundity and body length in the flood area. Several studies have identified a positive relationship between the number of oocytes and fish size (Adite et al, 2006;Brickle et al, 2005;Magalhães et al, 2003;Mazzoni & Silva, 2006;Moffett et al, 2006;Sato et al, 2006;Tarkan, 2006;Martins-Queiroz et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding these aspects can be considered the first step in establishing the principal life-history patterns of fish species and in determining recurrent patterns, which normally facilitate the prediction of behavior in a given period and geographic area (Matthews, 1998;Mazzoni & Silva, 2006). Individuals must reach a given age or size before they are able to reproduce.…”
Section: Introductionmentioning
confidence: 99%